Technical success rate of MR elastography in a population without known liver disease. - Gill, Howard E.; Lisanti, Christopher J.; Schwope, Ryan B.; Kim, Jason; Katz, Matthew; Harrison, Stephen (Abdominal Radiology, 2021)
Purpose: MR elastography (MRE) has a low technical failure rate in patients with chronic liver disease. The failure rate in an unscreened population is unknown. The purpose of this study was to determine the technical failure rate of MRE in patients with no known liver disease. Methods: In this prospective trial, 633 patients received 673 scans on a 1.5 T MRI using a standard gradient recalled echo MRE protocol. Four MRE images were acquired and repeated as necessary. Two investigators in consensus categorized each failure: 1. Anatomical masking failure; 2. Iron deposition; 3. No waves (connection problem); 4. Poor wave propagation; 5. Poor passive driver placement; 6. Patient breathing problems. Full exam failure was defined as no usable data in all slices. Partial failure was no usable data on at least one slice. Results: 1.0% (7/673) were full failures and 7.0% (47/673) were partial failures per patient. Full failures: iron deposition-71.4% (5/7); no waves-28.6% (2/7). 4.0% (108/2733) slice failure rate: Anatomical masking failure-31.5% (34/108); Iron deposition-25.0% (27/108); No waves-13.0% (14/108); Poor wave propagation-7.4% (8/108); Poor passive driver placement-11.1% (12/108); Patient breathing problems-12.0% (13/108). Conclusion: The failure rate of 1% is lower than for a screened population. Iron overload was implicated in most full failures. This study demonstrates the high technical success rate of MRE in an unscreened population laying the foundation for MRE as a possible screening tool for the general public.